Complex Regional Unification of Private International Law Rules on the Base of a Three-Part Structure: Political and Legal Framework - Berman, Alisa; Ershov, Nikita (Տիգրան Մեծ)
This article examines the theoretical and legal framework of a complex regional unification of private international law rules on the basis of a three-part structure. The authors analyzed reasons for spread of trends to regional unification of private international law. Special attention in the article is given to the definition of the content and essence of a complex regional unification. The authors define acts of complex unification as acts structured according to the principle of a consistent response to the questions of applicable law, jurisdiction, recognition and enforcement of foreign decisions in the regulated area. The article identifies the key advantages and disadvantages of a complex unification of private international law based on a three-part structure. The authors conclude that, to date, the adoption of acts of complex unification based on the three-part structure is one of the key trends in the unification of private international law.
Keywords: Methodology; Digitalization of law